Pengenalan Kirigami untuk Meningkatkan Kreativitas Siswa di MIS Halwani Gebang - Tuti Rezeki Awaliyah Siregar; Fahrunnisa Fahrunnisa; Dila Aulia; Sukri Agustian (FKIP, Universitas Palangka Raya, 2023)
This community service aims to develop and increase students' creativity by introducing kirigami, namely folding and cutting paper to form letters of the alphabet. The tools and materials used are paper, scissors and cutter. This activity was carried out on Thursday, September 15 2022 at MIS Halwani Gebang, Langkat Regency. The benefit of carrying out this activity is to improve the mathematical concept of geometry through the processes of folding, lining and cutting; improve students' fine motor skills by training their fingers in the process of folding paper; train students' concentration; foster a sense of community care by taking part in activities organized by the village, implementing kirigami skills in making backgrounds, congratulations, and so on; increasing students' creativity in the art of paper folding (kirigami).